The Role of the SDR in the International Monetary System - Roushdy, Juanita (Washington, D.C. : International Monetary Fund, 1987)
In the years since the SDR was created, the international monetary system has experienced a number of profound changes. The present paper sketches the effects of these changes on perceptions of the role that the SDR can and should play in that system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet